2023
DOI: 10.1002/cam4.5690
|View full text |Cite
|
Sign up to set email alerts
|

Gene mutation analysis using next‐generation sequencing and its clinical significance in patients with myeloid neoplasm: A multi‐center study from China

Abstract: Background Myeloid neoplasms (MN) tend to relapse and deteriorate. Exploring the genomic mutation landscape of MN using next‐generation sequencing (NGS) is a great measure to clarify the mechanism of oncogenesis and progression of MN. Methods This multicenter retrospective study investigated 303 patients with MN using NGS from 2019 to 2021. The characteristics of the mutation landscape in the MN subgroups and the clinical value of gene variants were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…NGS technology is a useful tool for discovering the genetic landscape and gene mutations of AML, and provides new molecular biomarkers for disease prognosis classification and targeted therapy [ 43 ]. Nevertheless, genetic mutations with prognostic value in AML patients have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…NGS technology is a useful tool for discovering the genetic landscape and gene mutations of AML, and provides new molecular biomarkers for disease prognosis classification and targeted therapy [ 43 ]. Nevertheless, genetic mutations with prognostic value in AML patients have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported in a cytogenetically heterogeneous cohort of 192 adult AML that patients with GATA2mut had significantly better overall and relapse-free survival (RFS) than those without GATA2 [ 22 ]. However, two other studies, also conducted in adult AML patients with cytogenetically heterogeneous backgrounds, found no discernible differences in survival between those with GATA2mut and those with wild-type GATA2 [ 23 , 24 ]. These conflicting results may result from the genetic heterogeneity of GATA2-mutated AML, such as different cytogenetic abnormalities and other molecular alterations.…”
Section: Introductionmentioning
confidence: 99%